Tinjauan Tentang Penggunaan OPAC di Perpustakaan Poltekkes Kemenkes RI Padang - Ramadhanu, Rahmat; Ardoni, Ardoni (Ilmu Informasi Perpustakaan dan Kearsipan, 2013)
The purpose of this paper is to obtain a description of (1) the use of the OPAC at Strathmore University Library polytechnic Padang, and (2) the constraints faced in the use of the OPAC at Strathmore University Library polytechnic Padang and solving problems in the use of the OPAC at Strathmore University Polytechnic Library Padang. The data was collected through observation and interviews with the head, staff and pemustaka at Strathmore University Library polytechnic Padang. The findings of the study, namely (1) OPAC is rarely used because pemustaka not know about the OPAC and OPAC computers to access has not been specified, (2) dissemination of the Library OPAC done polytechnic Strathmore University Padang yet effective, (3) a computer to search the OPAC yet devoted to access the OPAC. Keywords: library; information; OPAC